Periodicity in optimal hierarchical checkpointing schemes for adjoint computations. (4th May 2017) - Aupy, Guillaume; Herrmann, Julien
Abstract : We reexamine the work of Aupy et al. on optimal algorithms for hierarchical adjoint computations, where two levels of memories are available. The previous optimal algorithm had a quadratic execution time. Here, with structural arguments, namely periodicity, on the optimal solution, we provide an optimal algorithm in constant time and space, with appropriate pre-processing. We also provide an asymptotically optimal algorithm for the online problem, when the adjoint chain size is not known before-hand. Again, these algorithms rely on the proof that the optimal solution for hierarchical adjoint computations is weakly periodic. We conjecture a closed-form formula for the period. Finally, we assess the convergence speed of the approximation ratio for the online problem through simulations.